Neuromuscular spine deformities in cerebral palsy. Report from the 6th edition of the Transatlantic Orthopedic Surgery Webinar 2025 - Nowak, Paulina; Gruszecki, Jędrzej; Chambers, Hank; Graham, Kerr; Harasymczuk, Piotr; Howard, Jason; Johnson, Michael; Kotwicki, Tomasz; Lang, Robert S.; Miller, Freeman; Narayanan, Unni; Rodby-Bousquet, Elisabet ; 0000-0001-8373-1017; et al. (Chirurgia Narzadow Ruchu i Ortopedia Polska - Polish Orthopaedics, 2025)
Introduction. The sixth edition of the Transatlantic Orthopedic Surgery Webinar was held on March 3rd 2025, focusing on the comprehensive management of neuromuscular scoliosis in children with cerebral palsy (CP). The event brought together leading experts from Europe, North America, and Australia, representing centers of excellence in pediatric orthopedics and neuromuscular care. The initial session addressed the intertwined family, psychosocial, and pre-operative challenges associated with scoliosis in CP. Presentations highlighted the emotional, logistical, and financial burdens that families experience throughout the treatment journey. The limited efficacy of non-surgical interventions such as bracing and therapy was reviewed, alongside the confusion caused by conflicting information from various sources. The discussion emphasized how major surgery impacts not only the child but the entire family, intensifying caregiving demands and psychological stress. Anesthesia and pre-operative management were discussed as critical components of multidisciplinary care. Speakers underlined the importance of comprehensive pre-operative assessment, including evaluation of cardiac and pulmonary function, nutritional status, and comorbidities, and the need for careful risk stratification. Protocols for intraoperative safety were detailed, with a focus on temperature regulation, airway management, and multimodal pain strategies. The integration of these pre-operative practices with family-centered support was emphasized as essential for optimizing both clinical outcomes and the overall well-being of patients and caregivers. Surgical sessions explored current controversies and technical advances in the management of neuromuscular scoliosis. Topics included individualized decision-making regarding pelvic fixation – balancing the risks of implant failure in ambulatory patients with the need for stability in non-ambulatory children – and the limited but important role of growth-friendly implants. Detailed operative protocols were shared for posterior spinal fusion, including the two-surgeon approach, neuromonitoring, and infection prevention. The session on bipolar instrumentation presented minimally invasive alternatives for selected patients, demonstrating reduced operative morbidity and comparable radiographic outcomes. The management of complex, rigid deformities was addressed through algorithmic use of traction, staged procedures, and advanced osteotomy techniques, with an emphasis on tailored correction and pre-operative safety. Conclusions. Key conclusions from the webinar include: family-centered care and psychosocial support are essential throughout the management of neuromuscular scoliosis in CP, non-surgical treatments have limited impact on curve progression, and surgical intervention requires careful multidisciplinary planning, the choice of surgical technique-whether posterior fusion, bipolar instrumentation, or staged osteotomies – should be individualized based on patient functioning, curve characteristics, and comorbidities. Technical advances and pre-operative protocols have improved safety and outcomes, but ongoing collaboration and data sharing remain vital.
Keywords: bipolar instrumentation; cerebral palsy; family-centered care; neuromuscular scoliosis; osteotomy; pelvic fixation; pre-operative management; spinal fusion; traction